Osteoid Osteoma Mimicking Triangular Fibrocartilage Complex Injury: Diagnosis and Review of Treatment - J. M. Lamo-Espinosa; A. González; S. Amillo (Case Reports in Surgery, 2012)
We report the case of osteoid osteoma (OO) with ulnar styloid involvement. A review of the literature has been made with the aim of defining the special behaviour of OO when it is near the articular surface. That behaviour can affect the diagnosis, masking the real etiology of the pain, delaying the diagnosis, missing the diagnosis, or what is more serious, conducting an inadequate treatment. We propose a treatment algorithm conducted based on the localization near or far from articular surface and the superficial or deep localization.